Critical selection of scientific publication through axiological questions - Argota-Pérez, George (2023)
Axiological questions are barriers to identify methodological errors in the acceptance of scientific publications. The aim of the study was to describe the critical selection of scientific publication by means of axiological questions. The study was conducted in February 2023. Using non-probabilistic convenience sampling from Google Scholar, the 47 review articles from 2022 to 2023 were selected. Boolean signs were used where the search equation was in English language: "scientific writing" AND "scientific manuscript preparation" OR "scientific writing skills". The critical selection of the scientific publication by means of axiological questions described that there was a low number of citations, and perhaps the methodology was not detailed enough where 93.62% of the scientific articles presented less than 10 citations. It was concluded that the axiological questions on the scientific article enabled the contributory assessment. The number of citations in the scientific articles conditioned the possibility of reference.